The Impact of A1- and A2 β-Casein on Health Outcomes: A Comprehensive Review of Evidence from Human Studies - Nerea González-Rodríguez; Natalia Vázquez-Liz; Ana Rodríguez-Sampedro; Patricia Regal; Cristina Fente; Alexandre Lamas (Applied Sciences)
The digestion of A1 β-casein present in conventional milk releases β-casomorphin-7 (βCM-7), a bioactive peptide with potential implications for gastrointestinal and neurological health. A scoping review was performed to respond to the following research question: What are the health effects of consuming milk containing the A1 β-casein variant compared to the exclusive consumption of the A2 variant in humans? The evidence collected in this review of human studies with different populations (i.e., children, middle-aged adults, athletes) suggests that the consumption of milk containing A1 β-casein may negatively influence gut health by altering microbial composition, reducing intestinal motility, and increasing colonic fermentation, leading to elevated gas production and altered short-chain fatty acid (SCFA) profiles. The release of βCM-7 upon digestion can also compromise intestinal-barrier integrity, which may exacerbate symptoms of lactose intolerance, irritable bowel syndrome (IBS), or other allergy-related sensitivities. Its ability to cross the blood–brain barrier raises concerns about potential neurological effects. In contrast, milk containing exclusively A2 β-casein is associated with improved gastrointestinal outcomes, including the enhanced abundance of beneficial bacteria such as Bifidobacterium spp. and reduced inflammatory markers.